DYNAMICS OF THE PALM TREE SEEDLING BANK IN NATURAL ENVIRONMENT - TONETTI, Emerson Luiz; NEGRELLE, Raquel Rejane Bonato (Scientia Agraria, 2001)
The work was carried out at BANESTADO S/A Reflorestadora, in Paranaguá, Paraná (25º 35 S; 48º 32 O). Our intent was to contribute to the biology knowledge of Euterpe edulis Mart. in natural environment, to support future sustainable management plans. Specifically, we sought to estimate growth, survival, birth and transition rates of the juveniles (seedlings bank) for the period of one year. The survival pattern observed was similar to the ones already described in the literature, represented by high mortality rate among younger stages. The mortality caused by falling branches was very expressive. It was verified that growth in height, diameter and leaf production tend to increase at the older stages. The same holds true for the number of dead leaves. The birth, survival and transition rates obtained for the different stages under study indicate spontaneous natural regeneration of this species at the study site.